2016
DOI: 10.1111/cas.13059
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting autophagy increases epirubicin's cytotoxicity in breast cancer cells

Abstract: Chemotherapy, radiotherapy, and endocrinotherapy are documented to induce autophagy among breast cancer cells, but the role of autophagy in this disease has been attributed as cytoprotective as well as tumor‐suppressing. Thus we studied MDA‐MB‐231 and SK‐BR‐3 breast cancer cell lines treated with epirubicin (EPI) to assess autophagy and apoptosis. We found out that EPI induced apoptosis and autophagy in both cell lines. The lysosomal inhibitor bafilomycin A1 inhibited cellular autophagy and enhanced EPI‐trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Our previous study has found that EPI can induce autophagy in MCF‐7 breast cancer cells, which protects the cells from apoptosis . Guo et al subsequently obtained similar results in MDA‐MB‐231 and SK‐BR‐3 cells. However, Garbar et al report that multiple chemotherapy drugs, including EPI, induced an increase of autophagy in MCF‐7 cells, but not in MDA‐MB‐231 cells.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our previous study has found that EPI can induce autophagy in MCF‐7 breast cancer cells, which protects the cells from apoptosis . Guo et al subsequently obtained similar results in MDA‐MB‐231 and SK‐BR‐3 cells. However, Garbar et al report that multiple chemotherapy drugs, including EPI, induced an increase of autophagy in MCF‐7 cells, but not in MDA‐MB‐231 cells.…”
Section: Discussionmentioning
confidence: 68%
“…[7][8][9] Our previous study has found that EPI can induce autophagy in MCF-7 breast cancer cells, which protects the cells from apoptosis. 29 Guo et al 30 been published on the relationship between autophagy and cancer therapy, the mechanism by which autophagy participates in the treatment of cancer has not yet been fully established. [7][8][9] Here, we found that knockdown of Ambra1 blocked EPI-induced autophagy and increased the sensitivity of breast cancer cells to EPI.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB231 cells are endowed with a constitutively elevated autophagy rate. Inhibition of autophagy was proven to render them susceptible to the lethal effect of chemicals in various experimental conditions (e.g., [18,19,31,32]); on the other hand, lethal effects on this cell line induced by several autophagy inducers have been reported in the literature (e.g., [33,34]).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is substantiated by the absence of activation of cell death program, as observed after cell exposure to CF preparations. In fact, it is also known that autophagosomal degradation of the damaged mitochondria reduces the intracytoplasmic release of cytochrome C and inhibits the onset of intrinsic apoptosis [32]. It must also be taken into consideration, however, that MDA-MB-231 cells are provided with a mutant p53 and high levels of phospholipase D, both sustaining survival, thereby being intrinsically resistant to apoptosis [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a complex and controversial role in breast cancer, operating as either a tumor-suppressor system addressing neoplastic cells to death, or a cancer cell protective system which provides energy and basic elements to allow a fast-proliferative rate in conditions of oxygen and nutrient deficiency [36]. MDA-MB-231 cells are characterized by a constitutively elevated autophagy rate and autophagy restraining has made them vulnerable to cytotoxic treatments in various experimental conditions [20,21,37,38]. On the other hand, it is widely recognized that chemical induction of autophagy can be lethal to MDA-MB231 cells, as reported in some published papers [39,40].…”
Section: Discussionmentioning
confidence: 99%